(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Allophones are a key concept in phonology, the linguistic discipline that studies the sound structure of language. Allophones are different pronunciation variants of the same phoneme that can occur in different contexts. In this article, we’ll look at allophones in more detail, including their role, classification, and examples from different languages.